Pengaruh Konsumsi Sayur Daun Kacang Panjang terhadap Peningkatan Berat Badan pada Bayi Usia 0-6 bulan di PMB Nurya Viandika, M.Kes. - Firdasary, Yeyen Desiar (NHM PRESS, 2023)
According to the Indonesian Population and Health Survey (IDHS), coverage of exclusively breastfed infants in 2017 was 61.33%. One of the reasons mothers don't breastfeed is that the milk is weak and insufficient. Long bean leaf is a popular herb that is easily available and inexpensive. This Long bean leaf helps stimulate oxytocin and prolactin hormones such as alkaloids, saponins, polyphenols, steroids and flavonoids. The purpose of this study is to see the effect of giving Long bean leaves to increase milk production in pregnant mothers of infants aged 0-6 years in Midwifery Clinic Nurya Viandika, M.Kes. This research is a quantitative research with Quasi experiment. Quasi's experimental research conducted two observations, looking at milk production before and after receiving the yellow leaf. The statistical test used is the Paired Sample T-Test and the results of the analysis of the p value = 0.000 < α value (0.05), so H0 is rejected, which means that there is a significant difference between the weights. before treatment and body weight after treatment. This can also be seen from the value shown in the t-count value for increasing the number of babies before and after the intervention by giving Long bean leaves for 14 days is -5,529 with a probability (Sig.) 0.000. Therefore, it can be argued that feeding leafy vegetables can affect milk production.